A study on Vietnamese - English translation of cinematic hits’titles from 2013 to 2017 = Nghiên cứu về bản dịch Việt - Anh của tựa đề những bộ phim điện ảnh thành công từ năm 2013 đến năm 2017 - Nguyễn, Thị Lam Phương (ĐHQGHN - Trường Đại học Ngoại ngữ, 2020)
Along with the unprecedented development of the film industry, there is a growing number of Vietnamese movies being introduced worldwide and gaining certain achievements. As a result, movie title translation is receiving more and more attention, especially from scholars and researchers with quite many studies conducted in this field. However, the number of researches on translation of Vietnamese titles into English remains modest, which urged the researcher to do a study into this area, more specifically into the English translation of Vietnamese cinematic hits’ titles from 2013 to 2017. The study was divided into two phases corresponding to two research questions with samples of 20 titles and 30 participants. Phase 1 used qualitative approach to find out the translation techniques applied to translate ten chosen Vietnamese titles. Meanwhile, in phase 2, 30 participants- 15 Vietnamese people and 15 foreigners were asked to complete questionnaires to evaluate the extent to which original titles and their translations achieved three functions of a movie – informative, vocative and aesthetic function. The collected answers were converted to figures, and then presented by tables, allowing the researcher to obtain the findings and draw conclusions. Results from two phases revealed that Providing a new title and Literal translation were the two most common techniques employed for translating ten Vietnamese titles. Moreover, while there were two Vietnamese titles achieving all three functions, none of the translated titles could do it. In other words, all the English translated titles failed to achieve three assigned functions, as evaluated by target audience. Given the small population of the study, the researcher recommends further studies should be conducted with larger samples. Investigations into problems discussed in the study such as cultural elements in translation or the failure to fulfill three functions of translated titles should be encouraged